Decision-Making Regarding On-Farm Culling Methods for Dairy Cows Related to Cow Welfare, Sustainable Beef Production, and Farm Economics - Mariska Barten; Yvette de Geus; Joop den Hartog; Len Lipman (Animals)
In the Netherlands, around 52,000 dairy cows die on the primary farm each year due to natural death, euthanasia, or on-farm emergency slaughter (OFES). The decision as to what is the best option is made by the farmer, often after consulting a veterinarian, a livestock trader, or a slaughterhouse operator. To determine which factors play a role in this decision-making process, semi-structured interviews were conducted with dairy farmers, private veterinary practitioners, livestock traders, and slaughterhouse operators in the Netherlands. Dairy cattle culling decisions are influenced and limited by strict enforcement of livestock transport regulations and limited options for on-farm killing methods. Requirements regarding mortality rates imposed by the dairy industry and private quality labels for raw milk also influence culling decisions in the Netherlands. Most participants stated that restrictive conditions regarding OFES and mobile slaughterhouses (MSHs) appear to have (unintended) negative effects on cow welfare and meat salvage in general. Different interests, such as cow welfare, food safety, economic concerns of various stakeholders, the reputational interests of the dairy and beef industries, and sustainability objectives such as meat salvage can be conflictive. The results of this study show that the decision-making process regarding culling or (prolonged) veterinary treatment of dairy cattle is complex because various factors, interests, and uncertainties must be weighed. This weighing can vary between individual dairy farms and individual dairy farmers.